Konsep Pendidik dalam Al - Qur’an Surah Ar Rahman Ayat 1- 4 Menurut Quraish Shihab (Tafsir Al – Mishbah) - Rodliyah, Risalatur (Tinta Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Educators are the most important key in the world of education, educators not only teach in the learning process, but motivate, guide, students to achieve educational goals. However, recently it has been found that many educators who are supposed to be role models actually teach things that are contrary to the Qur'an. This research uses a type of library research (library research) using a content analysis approach model (content analysis). The data sources used are primary data sources and secondary data sources. The data collection technique used is documentation techniques. The data analysis used in this study is content analysis by analyzing and processing the contents of the data contained in the meaning content of surah ar rahman verses 1-4 about the concept of educators in the interpretation of al misbah by M Quraish Shihab. The results of this study show the existence of the concept of educator contained in surah ar rahman verses 1-4. In the tafsir al misbah by M Quraish Shihab there are characteristics of professional educators. According to Quraish Shihab in Tafsir Al Misbah this surah has relevance to Early Childhood Education in terms of having compassion towards learners, being knowledgeable, being able to shape personality and develop the potential of students, and having good communication skills.